A novel centrifugal gas liquid pipe separator for high velocity wet gas separation. (March 2020) - Wei, Pengkai; Wang, Dong; Niu, Pengman; Pang, Chenkang; Liu, Ming
Highlights: A novel centrifugal gas liquid pipe separator for high velocity wet gas separation is proposed. The centrifugal device of four semi-elliptic guide vanes can achieve a stable and uniform swirling core-annular flow. Nearly all swirling film can completely discharge from pipe relying on its own kinetic energy and inertial through NTC. With the increase of gas velocity, the abnormal change rules of separation efficiency are studied. The effect of structure parameters of NTC on separation efficiency is studied detailly. Abstract: Cyclones are the most widely used separators at present, but it's still difficult to reduce their size to serve as pipe separators. A new type of gas liquid pipe separator for high velocity wet gas is proposed in this paper. The separator is actually a short section of pipe, with a centrifugal device in the center portion and 3 narrow tangential conduits (NTC) in the pipe wall. As gas liquid mixture flows through the centrifugal device downwardly, a strong rotation flow is created. Liquid in the mixture is pushed to the pipe wall by centrifugal force and forms a uniform liquid film with high tangential velocity. Then nearly all the liquid film can directly enter the NTC and be discharged from the pipe relying on its own kinetic energy and inertial, because of the little resistance characteristic of NTC to the liquid film, therefore the whole separation process can be completed within the pipe. The swirl characteristics in the pipe were studied by numerical method, and the simulation results indicated that the swirling liquid film is fairly uniform and the suitable installation position for NTC is about 2.5 pipe diameters downstream of the centrifugal device. A separation model for the pipe separator was established and experiments were carried out to verify the proposed model. The superficial velocity ranges of gas and liquid were 22–72 m/s and 0.07–0.54 m/s, respectively. The experimental results showed that the separation efficiency always increases with the increase of both gas and liquid superficial velocity, generally it is over 0.81, and the maximum attainable is 0.97. However, the separation efficiency will begin to drop if liquid superficial velocity exceeds the critical value UCSL, due to the onset of unstable liquid film waves. Experimental results also showed that UCSL increases with the increase of gas velocity.